Production and propagation of heavy hadrons in air-shower simulators - García Canal, Carlos Alberto (2013)
Very energetic charm and bottom hadrons may be produced in the upper atmosphere when a primary cosmic ray or the leading hadron in an extensive air shower collide with a nucleon. At E≈108 GeV their decay length becomes of order 10 km, implying that they tend to interact in the air instead of decaying. Since the inelasticity in these collisions is much smaller than the one in proton and pion collisions, there could be rare events where a heavy-hadron component transports a significant amount of energy deep into the atmosphere. We have developed a module for the detailed simulation of these processes and have included it in a new version of the air shower simulator AIRES. We study the frequency, the energy distribution and the depth of charm and bottom production and decay in the atmosphere. As an illustration, we consider the production and decay of tau leptons (from Ds decays) and the lepton flux at PeV energies from a 30 EeV proton primary. The proper inclusion of charm and bottom hadrons in AIRES opens the possibility to search for air-shower observables that are sensitive to heavy quark effects.